The Effect of Genjer Leaf Extract Ointment (Limnocharis flava) on Incision Wounds in Male New Zealand White rabbits - Sefi Megawati; Saru Noliqo Rangkuti; Ilmi Hidayat; Avianti Eka Dewi Aditya Purwaningsih (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Incision wounds are a common type of open wound that require proper treatment to prevent infection and accelerate the healing process. The use of natural products as alternative wound therapy has been increasingly developed, one of which is yellow velvetleaf (Limnocharis flava), known to contain active compounds such as flavonoids, tannins, and saponins that have anti-inflammatory and wound healing properties. Objective: This study aimed to determine the effect of ethanol extract ointment of Limnocharis flava leaves on incision wound healing in male New Zealand White rabbits and to identify the most effective extract concentration. Methods: Limnocharis flava leaves were extracted using 70% ethanol by maceration with a ratio of 1:10, then formulated into ointments with concentrations of F1 (5%), F2 (7.5%), F3 (10%), F4 (negative control), and F5 (positive control using povidone-iodine). Results: The evaluation results showed that all ointment formulations met the physical requirements, including good homogeneity, stable form and color, pH compatible with skin pH, as well as optimal spreadability and adhesion. Observation of wound healing indicated an increase in the percentage of wound closure with higher extract concentrations and longer treatment duration. Statistical analysis using Two-Way ANOVA showed a p-value < 0.05, indicating a significant effect of extract concentration and duration of treatment on incision wound healing. Conclusion: Quantitatively, the 10% concentration group (F3) showed the highest percentage of wound closure and the fastest healing time compared to other groups, with effectiveness approaching the positive control. The 10% Limnocharis flava leaf extract ointment is the most effective formulation for accelerating incision wound healing.